Evaluation and protection of skin from cancer using conical dielectric probe - Abdul Khader Khan, Mohd; Najmus Saher, Sadia; Mohammad Iliyas, Dr. (International Journal of Engineering and Technology, 2018)
This present research paper proposes the usage of conical dielectric probe (CDP) for the identification, evaluation and protection of skin cancer. It is very easy to identify and cure skin tumors with the utilization of millimeter waves of size 95GHz or 35GHz called as dielectric probes. The response of this millimeter wave is very sensitive and reflective to water and so it is utilized in identifying the skin cancers. Such cancers have and parameter over that of healthy skin, and the probes spot cancers by recognizing these abnormal S-parameters utilizing COMSOL Multi physics software. Through experiment, evaluating the use of CDP and assure its protection as an optional for detecting the cancers of skin. Â Â